P252 Solid organ transplant (with the exception of liver) in patients with inflammatory bowel disease: An ECCO CONFER Multicentre Case Series. (30th January 2023) - Ribaldone, D G; Vieujean, S; Julsgaard, M; Zingone, F; Savarino, E; Cañete, F; Aratari, A; Imperatore, N; Ramos, L; Plaza, R; Pugliese, D; Barberio, B; et al.
Abstract: Background: There are limited data available on the course of IBD in patients with solid organ transplantation. The aim of this ECCO CONFER study was to evaluate the trend of IBD before and after solid organ transplantation but liver. Methods: This was a retrospective observational multicentre study that collected cases through the CONFER project. Patients with an established IBD diagnosis who underwent a solid organ transplantation (with the exception of liver) were eligible candidates. Results: 33 patients with solid organ transplantation (67% male; 55% CD) were collected from 12 referral centres in five different countries. Mean age was 53 ± 16 years. 34 organs were transplanted in 33 patients. Most of the patients underwent kidney transplantation (n=27, 82%). 4 (12%) received a heart and 1 (3%) underwent lung transplantation; 1 (3%) underwent a combined heart and kidney transplant. The mean duration of IBD was 18.4 ± 14.7 months. Clinical characteristics are summarized in Table 1. The median follow-up after transplantation was 4.3 years (IQR 3.25 – 10.7). 7/33 patients (21.2%) experienced organ rejection, with 1 kidney retransplant. Regarding immunosuppressive therapy, 29/33 patients (88%) were treated with tacrolimus, 25 (76%) with systemic steroids, 22 (67%) with mycophenolate mofetil, 11 (33%) with everolimus, 6 with cyclosporine (18%), 3 (9%) with thiopurines. Regarding biologics, 1 patient was treated with infliximab, 2 with adalimumab, 2 with vedolizumab, 1 with ustekinumab. Defining a severe IBD course the need for biologic therapy or bowel resection or hospitalization, 4 patients (11.7%) had a severe disease course after transplantation versus 3 patients (9.3%) in the first 51 months of disease before transplantation (p = 0.26). Univariate analysis is reported in Table 2. 1 case of low-grade dysplasia was found 10 years after the transplantation. 1 case of colorectal cancer was found in a patient affected by CD five years after kidney transplantation. The other cases of tumours after transplantation are reported in Table 3. The first serious infectious episode after transplantation is shown in Table 4: 17 of 33 patients (51.5%) reported at least 1 episode of serious infection. In total 29 different serious infectious episodes after transplantation were recorded, compared to 28 episodes in the pre-transplantation period. At the last follow-up visit, 6/33 (18.2%) patients had died: 1 due to cholangiocarcinoma, 1 amyloidosis, 1 heart failure, 1 myocardial infection (2 not available). Conclusion: Solid organ transplantation appears to have a satisfactory course for both the transplanted organ and IBD, in terms of organ survival and IBD severity; furthermore, the use of biologics in these patients does not appear to be linked to a worse outcome.